The Influence of the Madrasah Principal's Leadership Strategy and the Role of the Madrasah Committee on Improving the Quality Management of Facilities and Infrastructure in Cilegon City State MTS - Abdurrohman; Supardi; Qurtubi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The success of an educational institution is expected to be able to produce quality graduates, of course there is a need for a leadership strategy for the head of the madrasa/school as a leader or professional leader. So this study aims to determine the effect of the leadership strategy carried out by the head of the madrasa and the role of the committee on improving the quality management of facilities and infrastructure in Cilegon City State Madrasah Tsawiyah. The method used in this study is a correlational method with a quantitative approach. The reachable population is the teacher council at Madrasah Tsawiyah Negeri Se-Cilegon City 115 people. Based on the results of the study Based on the results of the multiple regression test, it can be seen that there is a significant influence between the leadership strategy of the madrasah head and the role of the madrasah committee on improving the quality management of facilities and infrastructure at the Cilegon City State Madrasah Tsanawiyah. This can be seen from the results That it is known that the values between variables X1 and X2 to Y are known that F count 62.329 > F table 3.294 at a significance level of 5%. In conclusion, Ha is accepted and Ho is rejected because of the influence between variables X1, Variable X2 and Variable Y. Then the results of the quantitative analysis in this study obtained the value r_(y1.2 =) 0.862 and R2 0.744 (74.4%) so that it affects quality improvement of facilities and infrastructure, as well as changes in the leadership strategy of the madrasa head and the role of the committee implemented in schools